2009
DOI: 10.1097/mbp.0b013e32832c5167
|View full text |Cite
|
Sign up to set email alerts
|

Consistent relationship between automated office blood pressure recorded in different settings

Abstract: Mean automated office BP readings are consistent from visit-to-visit regardless of the setting in which they are taken and they are similar to the mean awake ambulatory BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 13 publications
3
50
0
1
Order By: Relevance
“…Although AOBP in our study was recorded in a pharmacy setting, studies [16][17][18] have shown that AOBP readings are independent of the location in which they are taken, provided that the principles of AOBP are followed: multiple readings recorded automatically with the patient resting undisturbed in a quiet place. Of direct relevance to the present study, AOBP readings performed in community pharmacies using the CHAP protocol should be similar to the AOBP readings taken in the offices of the patients' own family physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Although AOBP in our study was recorded in a pharmacy setting, studies [16][17][18] have shown that AOBP readings are independent of the location in which they are taken, provided that the principles of AOBP are followed: multiple readings recorded automatically with the patient resting undisturbed in a quiet place. Of direct relevance to the present study, AOBP readings performed in community pharmacies using the CHAP protocol should be similar to the AOBP readings taken in the offices of the patients' own family physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Readings recorded in an ABPM unit or in an office waiting room are similar to AOBP recorded in a physician's examining room. [10][11][12] As a corollary to the present study, 275 residents aged over 65 years in 2 midsized communities in Ontario, Canada, had their BP recorded using standard AOBP procedures in a local pharmacy. 13 Mean AOBP values were similar to AOBP measurements taken on a visit to the subject's own family physician, indicating that AOBP-type measurements can also be taken in a pharmacy.…”
Section: Hypertensionmentioning
confidence: 96%
“…A recent study found no difference between AOBP obtained during a visit to the physician compared to readings taken in a nontreatment setting. 31 More than 14 000 individuals whose BP was recorded using the BpTRU device are currently being followed-up for cardiovascular morbidity and mortality to relate their BP levels to clinical endpoints. 32 A recent Canadian BP survey 33 of Ͼ2500 residents in the Province of Ontario successfully used the BpTRU to record BP.…”
Section: Recent Research Involving Aobpmentioning
confidence: 99%